Waning protection of influenza vaccine against mild laboratory confirmed influenza A(H3N2) and B in Spain, season 2014–15. Issue 20 (29th April 2016) - Gherasim, Alin; Pozo, Francisco; de Mateo, Salvador; Aspiritxaga Gamarra, Inma; García-Cenoz, Manuel; Vega, Tomas; Martínez, Eva; Giménez, Jaume; Castrillejo, Daniel; Larrauri, Amparo
Highlights: The 2014/15 influenza season in Spain was dominated by drifted A(H3N2) virus. The influenza vaccine effectiveness was low against influenza A(H3N2) and moderate against B virus. The influenza vaccine effectiveness decreased in late epidemic stage and with time since vaccination. The decrease of IVE was slower and milder against influenza B than against influenza A(H3N2). We highlight the importance of the influenza vaccination especially in population risk groups. Abstract: Introduction: The 2014/15 influenza season in Spain was dominated by the circulation of drifted A(H3N2) and co-circulation of B viruses. We present the final estimates of influenza vaccine effectiveness (IVE) against confirmed influenza A(H3N2) and B its evolution along the season and with time since vaccination. Methods: We used data collected on influenza like illness patients (ILI), systematically swabbed for the presence of influenza viruses within the Spanish Influenza Sentinel Surveillance System (SISS) and a restricted observational study (cycEVA). We used a test negative case–control design to compare influenza confirmed cases with negative controls. We estimated the IVE through a logistic regression model adjusting for potential confounders. The evolution of IVE was studied in early and late stages of the epidemic, and in different time intervals between receiving influenza vaccination and the onset of symptoms. Results: At the end of the season we have found low and moderate IVE point estimates against influenza A(H3N2) and B, respectively, in all ages and target groups for vaccination. An IVE decreased from an early value of 37% to a late of −76% against influenza A(H3N2), and similarly, 84% vs −4% against Influenza B. When the onset of symptoms occurred more than three months after vaccination, the decrease of IVE was slower and milder against influenza B than against influenza A(H3N2). No significant change in the percentage of circulating drifted influenza A(H3N2) strains belonging to the 3c.2a and 3c.3a clades could be identified through the season. Conclusions: In a season dominated by drifted A(H3N2) circulating virus, the vaccine offered little or no protection against A(H3N2) infection but had a moderate protective effect against influenza B. Efforts should be put in developing influenza vaccines that maintain their protective capabilities throughout the season and could stimulate a potentially broad immune response against diverse influenza strains.